Cellular human tissue-engineered skin substitutes investigated for deep and difficult to heal injuries - Álvaro Sierra-Sánchez (Nature Portfolio, 2021)
Abstract Wound healing is an important function of skin; however, after significant skin injury (burns) or in certain dermatological pathologies (chronic wounds), this important process can be deregulated or lost, resulting in severe complications. To avoid these, studies have focused on developing tissue-engineered skin substitutes (TESSs), which attempt to replace and regenerate the damaged skin. Autologous cultured epithelial substitutes (CESs) constituted of keratinocytes, allogeneic cultured dermal substitutes (CDSs) composed of biomaterials and fibroblasts and autologous composite skin substitutes (CSSs) comprised of biomaterials, keratinocytes and fibroblasts, have been the most studied clinical TESSs, reporting positive results for different pathological conditions. However, researchers’ purpose is to develop TESSs that resemble in a better way the human skin and its wound healing process. For this reason, they have also evaluated at preclinical level the incorporation of other human cell types such as melanocytes, Merkel and Langerhans cells, skin stem cells (SSCs), induced pluripotent stem cells (iPSCs) or mesenchymal stem cells (MSCs). Among these, MSCs have been also reported in clinical studies with hopeful results. Future perspectives in the field of human-TESSs are focused on improving in vivo animal models, incorporating immune cells, designing specific niches inside the biomaterials to increase stem cell potential and developing three-dimensional bioprinting strategies, with the final purpose of increasing patient’s health care. In this review we summarize the use of different human cell populations for preclinical and clinical TESSs under research, remarking their strengths and limitations and discuss the future perspectives, which could be useful for wound healing purposes.